The Phenomenon Of Doom That Befell The 'Ad In The Qur'an (Thematic Method) - Islam, Muhammad Thoriqul; Nurdiyanto, Nurdiyanto; Yulizar, Luqyana; Marjany, Nawa; Al Baqi, Safiruddin; Azwary, Khoula (Advances In Social Humanities Research, 2024)
The Qur'an is the greatest miracle revealed by Allah SWT to Prophet Muhammad (PBUH) as a guide for mankind. One of the main focuses of the Qur'an is to teach people about the worship of Allah, to warn against sins, and to give instructions for doing good in personal and social life. The phenomena and stories contained in the Qur'an are not just fairy tales but are a source of wisdom and knowledge that can be taken by humans. Through observation and understanding of the verses of the Qur'an, people are invited to draw closer to Allah and learn from the stories of the previous people. One example of the story recorded in the Qur'an is the destruction of the people of 'Ad, whom the Prophet Hud sent to warn them against idolatry. Despite warnings, the people of 'Ad remained in defiance, so Allah inflicted torment on them in the form of dark clouds that brought no rain, but strong winds and destruction.